Resistance of rice cultivars to Pyricularia oryzae in Southern Spain - Castejon Muñoz, M.=700 1 Lara Alvarez, I.; Aguilar, M.
(Es, En)
ilus., 16 ref.
Keywords: ORYZA SATIVA; RESISTENCIA A LA ENFERMEDAD; ENFERMEDADES FUNGOSAS; PYRICULARIA ORYZAE; ESPAÑA